Tinjauan Pelaksanaan Pemeliharaan Dokumen Rekam Medis di Ruang Filling RSUP Dr. Sardjito - Tias Agustin Ayuningrum; Gamasiano Alfiansyah; Sugeng Sugeng; Sustin Farlinda (Politeknik Negeri Jember, 2020)
The implementation of maintenance medical record documents in RSUP Dr. Sardjito is not optimal. This statement was proven by the damage of medical record documents about 35,05%. The purpose of this research is to review the implementation of maintenance medical record documents uses management elements 5M (man, money, material, machine, and method). The research type is qualitative and the data collection techniques use interviews, observations, and documentations. The subjects of this research are filling officers. The result from man factor shown that filling officers have not received maintenance medical record documents training, meanwhile money factor shown that filling officers did not know about the budget management of maintenance medical record documents. The result from material factor show that the materials for medical records forms and folders have been provided optimally, meanwhile machine factor shown that the type of rack from combination of iron and wood was less suitable because it can made medical record documents were damage. The result from method factor show that standard operational procedure about implementation of maintenance medical record documents was not available. The solutions are giving socialization about implementation of maintenance medical record documents to filling officers, providing standard operational procedure about implementation of maintenance medical record documents, coating around the sharp part of rack using rubber tires that can prevent the damage of medical record folder.